SANKSI HUKUM PIDANA TERHADAP PELAKU TINDAK PIDANA PENGGELAPAN DANA (ANALISIS PUTUSAN NOMOR: 1073/PID/2024/PT MDN) - Gunawan, Adinda Julia; Saragih, Yasmirah Mandasari; Ramadhani, Suci (Ensiklopedia of Journal, 2025)
Abstract: The crime of embezzlement in the legal sense is an unlawful act by hiding goods/property belonging to another person by one or more people without the knowledge of the owner of the goods with the aim of controlling or using them for other purposes. The purpose of this study is to analyze the law enforcement of the crime of embezzlement according to the law and to find out the causes of embezzlement and what sanctions are given to perpetrators of the crime of embezzlement in the Medan High Court decision with case number 1073/Pid/2024 Pt Mdn. The nature  research uses descriptive. This type of research is normative research while the data collection method uses library research and the type of data in study uses secondary data. Law enforcement of perpetrators of the crime of embezzlement is regulated in Articles 372-377 of the Criminal Code. The crime of embezzlement that the author raises is the crime of embezzlement of funds committed by the defendant who is proven to have embezzled funds, the defendant's actions are subject to criminal sanctions in Article 372 of the Criminal Code and impose a sentence on the defendant with 2 years in prison.Keywords: Embezzlement of  funds; Criminal sanctions; Criminal act.